PEMBELAJARAN KOOPERATIF TIPE TAI BERDASARKAN TEORI BEBAN KOGNITIF - RESTU RIA WANTIKA (Universitas PGRI Adi Buana, 2017)
The purpose of this study was to describe the study of mathematics used by cognitive load theory. According to the theory of cognitive load, cognitive load of learners consists of intrinsic cognitive load, extraneous and germane cognitive load. By managing the intrinsic cognitive load, reducing extraneous cognitive load, and increase germane cognitive load on the learner, the processing of information on learners can be more effective. The study examines the stages in cooperative learning TAI is based on the theory of cognitive load. Of each phase shown any cognitive load that appear and effectiveness in pembelajran. Results of the study is the emergence kognitifintrinsic load, extraneous, and germane learners in mathematics using didscovery methods, and the characteristics of the cognitive load that is intrinsic, extraneous, and germane learners in every phase of cooperative learning TAI type.